Multiple myeloma epidemiology and survival: A unique malignancy - Kazandjian, Dickran (Seminars in oncology, 2016)
Multiple myeloma (MM), although a rare disease, is the second most common hematologic malignancy. It is found in the spectrum of plasma cell dyscrasias, which begins with monoclonal gammopathy of unknown significance (MGUS) to overt plasma cell leukemia and extramedullary myeloma. MM is associated with significant morbidity due to its end-organ destruction. It is a disease of the older population and its incidence in the African American population is twice that of the European American population. Improvements in the treatment of MM in the past couple of decades, beginning with the use of autologous stem cell transplantation followed by availability of novel treatments such as immunomodulatory drugs (ImIDs) and proteasome inhibitors (PIs) has transformed the natural history of the disease leading to longer survival times. Advancements in the diagnosis, monitoring, and treatment of MM are of the utmost importance as the general population lives longer due to other improvements in health care. The recent introduction of novel therapies has been paralleled by advancements in the monitoring of MM, namely, by the availability exquisitely sensitive techniques in detecting minimal residual disease. As drug development and technology continues to improve, it will be important to design rationale clinical trials enrolling patient populations that represent the overall population, including racial minorities and the elderly, so that trial results can be appropriately extrapolated. Herein, the changing epidemiology, improvements in survival, and the health disparity observed in important subgroups of MM are reviewed.